Cha-One Sdn. Bhd. / Muhamad Haziq Haslan … [et al.] - Haslan, Muhamad Haziq; Harun, Dzulkifli; Sabri, Tun Amir Audi; Mokhlas, Izzat Farhan; Mohd Zulkifli, Mohd Saifuddin (2016)
After observation towards the existing tumbler in the market, the team had come out with product which can potentially contribute to the university student and office worker lifestyle. Starbuck, Dunkin Donuts, Coffee Bean and Tea leaf and other coffee shops have come up with small portable tumblers that can carry their coffee or tea to almost everywhere they go. Cha-One Sdn Bhd took this factor as an advantage and huge opportunity to create our product by providing technology improved tumblers that can ease consumer's busy lifestyle. Cha-One tumbler is a tumbler that has automatic stir function and system which allow user to control the temperature of their drink. Cha-One tumbler also has anti-spill lid mechanism that can prevent spillage of drink. This project blueprint is done to attract agency to apply for grant.